A polynomial-time approximation algorithm for the permanent of a matrix with nonnegative entries. - Jerrum, Mark (Journal of the ACM)
We present a polynomial-time randomized algorithm for estimating the permanent of an arbitrary n × n matrix with nonnegative entries. This algorithm---technically a "fully-polynomial randomized approximation scheme"---computes an approximation that is, with high probability, within arbitrarily small specified relative error of the true value of the permanent.